Tourist’s Willingness to Pay toward Waste Management in Mount Salak Endah Tourism Area, Bogor District - Kiki Yulia; Hadi Susilo Arifin; Meti Ekayani (Journal of Natural Resources and Environmental Management, 2022)
Mount Salak Endah (GSE) Natural Tourism Area is one of the tourism destinations in the conservation area of Mount Halimun Salak National Park, which is located in Bogor District. GSE is easy to reached, whether from Bogor or Jakarta. GSE has various beautiful natural destinations such as Cigamea Waterfalls, Kondang Waterfalls and hot spring attracting many visitors. The numbers of visitors keep increasing every year, but it is impacted to environmental problem, i.e. and in the end, it causes environmental problem: waste generation. The objectives of this study are (1) to identify and explore tourist perceptions regarding current and future waste management in the GSE natural tourism area and (2) Calculating the tourist’s willingness to pay related to the implementation of tourist-based waste management in GSE natural tourism area. This study used a Likert scale data collection method and Contingent Valuation Method (CVM). The tourist’s perception regarding waste management in the GSE natural tourism area shows positive result where tourists are willing to manage their waste with deposit refund.